Small Arms and Light Weapons Proliferation in West Africa: Implication for Nigerian Security - Ibrahim , Bashir; Abdulqadir, Yahaya (Kashere Journal of Politics and International Relations, 2025)
The proliferation of Small Arms and Light Weapons (SALW) in West Africa poses significant threats to regional and national security particularly Nigeria. This paper attempts to assess the implication Small Arms and Light Weapons Proliferation in West African Sub-region on Nigerian Security. To achieve this, the paper employed content analysis to x-ray the existing literatures on the central theme of the paper. The paper found that, West African sub-region is now awash with Small Arms and Light Weapons (SALW) of the approximately 500 million illicit weapons in circulation worldwide. This unfortunate situation is intricately connected with the strategic location of the West-African Sub-Region at the seaboard of Atlantic Ocean. The paper also found that SALW proliferation in West Africa fueled insurgency, banditry, kidnapping for ransoms, farmers-herders’ conflicts, electoral violence, etc. in Nigeria, thereby exacerbating humanitarian crises and undermining the state authority. The paper concludes that it would be meaningless to talk of comprehensive security in Nigeria in the midst of absence of good governance and pervasive leadership crises demonstrated in the form of absence of political will and commitment by our political actors to consciously implement programmes and policies that would promote socio-economic well-being of the country and also to embrace vital aspects of social and national development, such as the provision of employment opportunities and other basic social amenities that are vital for satisfying individuals’ basic needs.